When Machines Become Listeners: Emotional Intimacy of Human with AI - Christy Gabriella Hutagalung; Ilyas Dzaky Almahdy; Kamila Putri Nursyahbani; Muhammad Farhan Indra; Novita Nurafifah; Elizabeth Kristi Poerwandari (About the Journal, 2026)
The rapid integration of Artificial Intelligence (AI) into daily life has expanded its role from technical assistance to emotional companionship among young adults. This study aims to explore subjective experiences of emotional intimacy with generative AI chatbots, such as ChatGPT. Employing an interpretive qualitative design and reflexive thematic analysis, semi-structured interviews were conducted with five participants, including university students and early-career professionals. Four primary themes emerged: AI as an emotionally safe space, the attainment of validation and psychological relief, AI’s role as a partner for cognitive reflection, and the critical awareness of its limitations and ethical risks. The findings indicate that while AI facilitates short-term emotion regulation through non-judgmental availability, users maintain a clear distinction between algorithmic empathy and authentic human connection. This research underscores the necessity of emotional digital literacy and suggests that AI should be integrated as a complementary scaffold, rather than a substitute, for professional mental health support and interpersonal relationships.Penelitian ini dilatarbelakangi oleh pergeseran fungsi kecerdasan buatan (AI) dari sekadar alat produktivitas menjadi mitra interaksi emosional di kalangan dewasa muda. Tujuan penelitian ini adalah untuk mengeksplorasi pengalaman subjektif individu dalam membangun keintiman emosional dengan chatbot AI generatif seperti ChatGPT. Dengan menggunakan desain kualitatif interpretatif dan analisis tematik refleksif, wawancara semi-terstruktur dilakukan terhadap lima partisipan yang terdiri atas mahasiswa dan profesional awal karier. Hasil penelitian mengidentifikasi empat tema utama: AI sebagai ruang aman emosional, pencapaian validasi dan kelegaan psikologis, fungsi AI sebagai mitra refleksi kognitif, serta kesadaran kritis terhadap batasan etika dan risiko ketergantungan. Temuan ini menunjukkan bahwa meskipun AI efektif dalam membantu regulasi emosi jangka pendek, pengguna tetap mempertahankan batasan antara hubungan artifisial dan autentik. Implikasi penelitian ini menekankan pentingnya literasi digital emosional dan integrasi AI sebagai instrumen pendukung, bukan pengganti, dalam layanan kesehatan mental dan pendidikan.